Introduction to optical mineralogy - Nesse, William D. (Oxford University Press, 2013)
"Introduction to Optical Mineralogy provides comprehensive coverage of the optical properties of minerals. It describes in detail more that 125 rock-forming minerals and a selection of common ore minerals. Revised chapters on optical theory discuss the petrographic microscope, the nature and properties of light, the behavior of light in isotropic and anisotropic materials, and uniaxial and biaxial anisotropic optics. It is ideal for advanced undergraduate and graduate courses in optical mineralogy, this accessible text is also an essential resource for petrology/petrography courses"--